1953
DOI: 10.1177/00220345530320042001
|View full text |Cite
|
Sign up to set email alerts
|

The Amino Acid Composition of Enamel Protein

Abstract: B Y THE use of paper chromatography, Block, Horwitt, and Bolling' showed qualitatively that human enamel eukeratin contained most of the known amino acids, and gave quantitative values for arginine, histidine, and lysine.Losee and Hess,2 who had prepared the protein analyzed by Block, Horwitt, and Bolling, determined cystine, methionine, and phenylalanine by colorimetric methods and subsequently3 also determined arginine, histidine, and lysine, and confirmed the statement that the normal enamel protein is an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1960
1960
2008
2008

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…25-30% collagen, very many carefully prepared teeth must be utilized. The use of samples that are either of inadequate size, or not completely free of dentine or cementum, combined with extensive dialysis of material that is largely diffusible, has in the past resulted in either the recovery of insufficient amounts ofmaterial for even a single amino acid analysis (Piez, 1962), or the recovery of collagen-like proteins, presumably from the adjacent tissue layers (Hess, Lee & Neidig, 1953;Stack, 1954;Battistone & Burnett, 1956;Rodriguez & Hess, 1963).…”
Section: Discussionmentioning
confidence: 99%
“…25-30% collagen, very many carefully prepared teeth must be utilized. The use of samples that are either of inadequate size, or not completely free of dentine or cementum, combined with extensive dialysis of material that is largely diffusible, has in the past resulted in either the recovery of insufficient amounts ofmaterial for even a single amino acid analysis (Piez, 1962), or the recovery of collagen-like proteins, presumably from the adjacent tissue layers (Hess, Lee & Neidig, 1953;Stack, 1954;Battistone & Burnett, 1956;Rodriguez & Hess, 1963).…”
Section: Discussionmentioning
confidence: 99%
“…Early efforts to define the amino acid composition of human enamel proteins isolated the insoluble protein components of decalcified mature human enamel [51][52][53]. These studies used the various microbiologic methods available at the time [51,53] or paper chromatography [52], to roughly define the enamel amino acid composition.…”
Section: The Organic Matrix Componentsmentioning
confidence: 99%
“…These studies used the various microbiologic methods available at the time [51,53] or paper chromatography [52], to roughly define the enamel amino acid composition. However, because of the mature stage of the enamel used in these studies, most of the enamel proteins, as we know them today, were not characterized.…”
Section: The Organic Matrix Componentsmentioning
confidence: 99%
“…and 42%, respectively [2-4]. Citrate and lactate ions are also present in microquantities [5], whereas only traces of carbohydrate have been detected [6].Many studies have reported amino acid compositions for the human enamel matrix [7][8][9][10][11][12][13][14]. The main amino acids described were alanine, glutamic acid, glycine, proline, and serine.…”
mentioning
confidence: 99%